2015
DOI: 10.1002/hbm.23041
|View full text |Cite
|
Sign up to set email alerts
|

Differences in neural activity when processing emotional arousal and valence in autism spectrum disorders

Abstract: Individuals with autism spectrum disorders (ASD) often have difficulty recognizing and interpreting facial expressions of emotion, which may impair their ability to navigate and communicate successfully in their social, interpersonal environments. Characterizing specific differences between individuals with ASD and their typically-developing (TD) counterparts in the neural activity subserving their experience of emotional faces may provide distinct targets for ASD interventions. Thus we used functional magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Multivariate analyses can detect both differences in the average response over whole brain regions, like traditional univariate measures, but are also sensitive to relative differences in the spatial patterns of response. In typically developing adults, many cortical regions show similar overall magnitude, but distinct spatial patterns, of activity in response to positive versus negative facial expressions (Tseng et al, 2016). In the few previous studies using MVPA in participants with ASD, MVPA revealed differences in social information processing in individuals with ASD that were not detected with univariate methods (Coutanche et al, 2011; Gilbert, Meuwese, Towgood, Frith, & Burgess, 2009; Koster-Hale et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analyses can detect both differences in the average response over whole brain regions, like traditional univariate measures, but are also sensitive to relative differences in the spatial patterns of response. In typically developing adults, many cortical regions show similar overall magnitude, but distinct spatial patterns, of activity in response to positive versus negative facial expressions (Tseng et al, 2016). In the few previous studies using MVPA in participants with ASD, MVPA revealed differences in social information processing in individuals with ASD that were not detected with univariate methods (Coutanche et al, 2011; Gilbert, Meuwese, Towgood, Frith, & Burgess, 2009; Koster-Hale et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, understanding of automatic emotion processing in the disorder can provide better understanding and clarification of specificity of emotion processing in this group. The importance of understanding various aspects of emotion processing is particularly evident from a recent study (Tseng et al, 2016 ) that showed differences in neural activity for arousal but not valence on emotion processing between subjects with autism and neurotypically developing subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of an online (restaurant) review, disgust is a very relevant and often-communicated emotion (Ahmad & Laroche, 2015). It is considered a high arousal emotion (Tseng et al, 2016) that, like anger, can be perceived as a moral emotion (Hutcherson & Gross, 2011). Disgust may be appropriate to communicate in the context of an online review about a restaurant experience, as it is often expressed in response to both food intake (Rozin et al, 1999) and service encounters (Johnson & Zinkhan, 1991).…”
Section: Discussionmentioning
confidence: 99%